2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5160026
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling for finite time consensus

Abstract: Abstract-We study the problem of link scheduling for discrete-time agents to achieve average consensus in finite time under communication constraints. We provide necessary and sufficient conditions under which finite time consensus is possible. Furthermore, we prove bounds on the consensus time and exhibit provably optimal communication policies. We also discuss the dual problem of designing communication schedules given a fixed consensus-time requirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We call the above method of implementing Algorithm 1 and consensus protocol (10) simultaneously as ADMM live. Now, we compare the performance of ADMM live with the Metropolis weights using the following example.…”
Section: B New Agents Enter a Network: Admm Live -A Variation Of Algo...mentioning
confidence: 99%
See 1 more Smart Citation
“…We call the above method of implementing Algorithm 1 and consensus protocol (10) simultaneously as ADMM live. Now, we compare the performance of ADMM live with the Metropolis weights using the following example.…”
Section: B New Agents Enter a Network: Admm Live -A Variation Of Algo...mentioning
confidence: 99%
“…In all consensus protocols, an important parameter is the time required to reach average consensus. One line of literature focuses on algorithms which achieve consensus in finite time [8]- [10]. The other line of literature looks at algorithms which achieve consensus asymptotically, while trying to improve the rate of this asymptotic convergence [6], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our work is most closely related to [17] where Ko and Shi examined link scheduling on the complete graph to achieve finite-time average-consensus. They provided necessary and sufficient conditions for finite-time consensus and computed the minimum consensus time on the boolean hypercube.…”
Section: Related Workmentioning
confidence: 99%
“…Boyd et al [13] studies the ǫ-average time of (2) when the W (t)'s are drawn independently and uniformly at random from S ′ 1 ∩G. In terms of finite-time consensus, [17] showed that …”
Section: G-admissible Factorizationmentioning
confidence: 99%
See 1 more Smart Citation